Pain Relief After Knee Arthroscopy: Intra-articular Morphine, Intra-articular Bupivacaine, or Subcutaneous Morphine?: Intra-articular Morphine, Intra-articular Bupivacaine, or Subcutaneous Morphine? - Soledad M. Cepeda; Carlos Uribe; Jairo Betancourt; Jose Rugeles; Daniel B. Carr (Regional Anesthesia: The Journal of Neural Blockade in Obstetrics, Surgery, & Pain Control, 1997)
Background and Objectives This investigation was undertaken to compare analgesic effects, side effects, and requirements for supplemental analgesic therapy after knee arthroscopy in patients given intra-articular (IA) or subcutaneous (SC) morphine, intra-articular bupivacaine, or placebo. Methods In a randomized, double-blind controlled trial, 112 patients, 14-65 years old each received two solutions, one SC and the other IA. Group IAM (n = 30) received 10 mg IA morphine in 20 mL normal saline plus 1 mL of SC normal saline Group IAB (n = 27) received 20 mL IA bupivacaine 0.5% with IA epinephrine plus 1 mL SC normal saline Group SCM (n = 26) received 20 mL IA normal saline plus 10 mg SC morphine in 1 mL. Group P (n = 29) received 20 mL IA normal saline plus 1 mL SC normal saline. Pain was evaluated on arrival in the postanesthesia care unit (PACU), and 30, 45, 60, 90, and 120 minutes afterwards. If pain exceeded 4/10 on a visual analog pain scale in the PACU, 30 mg intravenous ketorolac was given, and if pain persisted, 0.4 mg hydromorphone was added every 7 minutes. After PACU discharge, patients whose pain exceeded 4/10 received oral ketorolac 10 mg every 6 hours; oral acetaminophen plus codeine was added every 4 hours if pain still exceeded 4/10. Analgesic requirements, along with visual analog pain score, sedation, and nausea were recorded every 6 hours for 72 hours. Results All three active (nonplacebo) pain treatments provided good pain control in the PACU. Side effects were similar in all groups. The placebo group had higher pain scores at 120 minutes ( R = .02), higher supplemental analgesic requirements at 60 minutes ( P = .04) and 90 minutes ( P = .02) and the highest amount of total opioid rescue dose ( P = .04). Patients in groups IAB and P had higher visual analog pain scores at 6 hours ( P = .04) and 30 hours ( P = .049) than those in Groups IAM and SCM. Conclusion A single 10-mg dose of morphine given either IA or SC provides better and longer-lasting postoperative pain relief after knee arthroscopy than 20 mL IA bupivacaine 0.5% with epinephrine.